CALCULATION OF BUCKLING PIPE FOR PIPE SIZE 10", 40" AND 56" CROSSING AT NUCLEAR POWER PLANT - Syamsurrijal Ramdja; Achmad Chamsudi (Jurnal Perangkat Nuklir, 2013)
The actually buried pipe crossing in the project of NPP (Nuclear Power Plant) installation to be found the self problem for installation, especially if the crossing will be subjected to loads of vehicle traffics and weight of soil, this pipe shall be make sure is not buckling during operation with deflection calculation shall be lest then 1 ratio between radius of pipe  Pada proyek pekerjaan instalasi PLTN (Pembangkit Listrik Tenaga Nuklir) di lapangan sering ditemukan permasalahan instalasi silang pipa benam khususnya persilangan dengan ja/an yang memuat beban arus kendaraan dan beban berat tanah. Kalkulasi ini bertujuan untuk memastikan tidak terjadi buckling pada pip a selama operasi yang tidak melebihi dari 1 dibandingkan dengan radius pipa.